Phosphorus bioavailability of sewage sludge‐based recycled fertilizers in an organically managed field experiment. Issue 5 (1st August 2018) - Wollmann, Iris; Möller, Kurt
Abstract: Recycled phosphorus (P) fertilizers from sewage sludge can contribute to the ongoing effort of closing the P cycle. Five recycled P fertilizers (Struvite SSL, Struvite AirPrex®, P‐RoC®, Pyrolysis coal, and Na‐SSA) were tested for their P availability in a two‐year field experiment with maize. The experiment was conducted on an organic certified research station at soil pH 6.5. Other P fertilizer treatments included: phosphate rock (PR), compost, and an unfertilized control. In addition, the rhizobacteria strain Bacillus sp . Proradix (Proradix®) was applied to test its ability to increase P bioavailability. Each year, shoot DM and P offtake of maize was measured and P use efficiency of the tested fertilizers was calculated. No significant differences in shoot DM were found among fertilized treatments and the unfertilized control in both years of experiment. Fertilization with recycled fertilizers increased P offtake by between 0% (Na‐SSA) and 27.5% (Struvite SSL) compared to the unfertilized control. Rhizobacteria application led to an increase in P offtake of maize from 25.9 to 38.7 kg P ha −1 when combined with PR fertilization in the year of fertilizer application, while no significant effect was found for the recycled fertilizers. Some of the tested recycled fertilizers from urban waste water can be considered as effective fertilizers for their use in organic agriculture.